Advanced glycation end products promote VEGF expression and thus choroidal neovascularization via Cyr61-PI3K/AKT signaling pathway. Issue 1 (December 2017) - Sun, Lijuan; Huang, Tonglie; Xu, Wenqin; Sun, Jiaxing; Lv, Yang; Wang, Yusheng
Abstract Choroidal neovascularisation (CNV) causes severe vision loss among old patients, especially those with diabetes. Previously, Cyr61 has been found to play a critical role in the pathogenesis of both AMD and diabetes. In the present study, we found that increased CNV severity together with higher expression of Cyr61 and VEGF in diabetes mice compared with control mice. Moreover, knockdown of Cyr61 decreased CNV severity.In vitro mechanism study revealed that the advanced glycation end products (AGEs) significantly increased the expression of Cyr61 in retinal pigment epithelial (RPE) cells, mimicking the effects of diabetes. In turn, the increased Cyr61 enhanced VEGF expression through FAK and PI3K/Akt pathways. Chemically blocking the above pathway significantly inhibited CNV formation, providing a new strategy for clinical prevention and treatment of CNV in related diseases.